THE URGENCY OF FINGERPRINTS AS EVIDENCE IN CRIMINAL JUSTICE PROCEEDINGS - Krismiyarsi, Krismiyarsi; Soleh, Adi Nur; Karyono, Hadi; Pancawisma, Mahmuda (Universitas 17 Agustus 1945 Semarang, 2024)
The Stages in the criminal justice process, starting from the investigation, prosecution, examination before the court, to the implementation of the court decision or execution. At each stage there are several actions that must be taken to be able to enter the next stage. Fingerprints are lines found on the skin of the fingertips of a person's right and left hands. The fingerprints of criminals are often left at the crime scene. Inquiries and investigations as one of the stages in the criminal justice process are intended to make clear and clear a criminal case in order to find the perpetrator. In carrying out inquiries and investigations, it is necessary to secure the place where the crime occurred to carry out fingerprint identification of the victim or perpetrator of the crime. This research uses a normative juridical research type with a statutory approach, concept approach and case approach. Using secondary data as main data through: statutory regulations, literature books, and criminal cases. Analysis uses qualitative analysis. The aim of this research is to analyze the urgency of fingerprints as evidence in the criminal justice process. The results of the research show that: The urgency of fingerprints in the criminal justice process is that apart from having an important function in the inquiry and investigation stages, they are also important as evidence for expert testimony, documentary evidence and indicative evidence in the evidentiary process at court hearings. Apart from being a piece of evidence, the perpetrator's fingerprints also function as evidence at trial, because the fingerprints on the tools used to commit the crime are accurate evidence regarding who the perpetrator was.